Political Values in the Books of Social Studies in Basic Fifth and Sixth Grades (Journal of Hama University, 2024)
The current research aims at defining political values that must be available in the books of Social Studies in basic fifth and sixth grades, and recognizing the availability of political values in these books. The researcher has used the descriptive analytical approach. She has analysed the content of the books of social studies. She has used the idea as a unit for analysis. The units analysed are the political values that must be available in the books of social studies in basic fifth and sixth grades. The research community consists of the curriculums of social studies in basic fifth and sixth grades in Syrian Arab Republic. The research sample consists of the books of social studies in basic fifth and sixth grades in Syrian Arab Republic for the academic year 2022- 2023. The research had the following results:- The political values that must be available in the books of social studies in basic fifth and sixth grades are (13): loyalty, belongingness, and love of homeland- national unity- participation- collective responsibility- appreciation of political power- appreciation of security men in preserving homeland- forgiveness- justice and equality- democracy- capability of discussion and negotiation- respect of diversity and pluralism- resorting to law- taking responsibility.- The political values available the Books of Social Studies in Basic Fifth and Sixth Grades are repeated (278) times with a percentage of (38.39%) of the overall number of analysis units. The book of sixth grade includes (155) political values with a percentage of (42.46%) out of the overall values available in the book. The book of fifth grade includes (123) values with a percentage of (34.26%).- The values occurred in both books have the following order: the value of loyalty, belongingness, and love of homeland, participation, capability of discussion and negotiation, taking responsibility, forgiveness, - The value of loyalty, belongingness, and love of homeland is the most repeated value in the book of fifth grade. However, this book does not include any of the following values: national unity, appreciation of political power, appreciation of security men in preserving homeland, democracy.- The value of loyalty, belongingness, and love of homeland is the most repeated value in the book of sixth grade. The values of appreciation of political power and resorting to law come last.